Academic surgery in the UK and the Surgical Research Society 50 years ago. (2nd October 2020) - Ellis, Harold
Abstract : Fifty years ago, in 1970, academic surgical units had finally been established throughout the universities in the UK. Such departments had been created in the Scottish university cities in the 19th century; some medical schools in London had resisted this custom, but by now these bastions of the old system had surrendered!